Nitrogen-fixing bacteria boost floral attractiveness in a tropical legume species during nutrient limitation - Souza, Caroline; Valadão-Mendes, Lorena B.; Schulze-Albuquerque, Isadora; Bergamo, Pedro J. [UNESP]; Souza, Douglas D.; Nogueira, Anselmo (Wiley, 2024)
Premise: Legumes establish mutualistic interactions with pollinators and nitrogen (N)-fixing bacteria that are critical for plant reproduction and ecosystem functioning. However, we know little about how N-fixing bacteria and soil nutrient availability affect plant attractiveness to pollinators. Methods: In a two-factorial greenhouse experiment to assess the impact of N-fixing bacteria and soil types on floral traits and attractiveness to pollinators in Chamaecrista latistipula (Fabaceae), plants were inoculated with N-fixing bacteria (NF+) or not (NF-) and grown in N-rich organic soil (+N organic soil) or N-poor sand soil (-N sand soil). We counted buds and flowers and measured plant size during the experiment. We also measured leaf, petal, and anther reflectance with a spectrophotometer and analyzed reflectance curves. Using the bee hexagon model, we estimated chromatic contrasts, a crucial visual cues for attracting bees that are nearby and more distant. Results: NF+ plants in -N sand soil had a high floral display and color contrasts. On the other hand, NF- plants and/or plants in +N organic soil had severely reduced floral display and color contrasts, decreasing floral attractiveness to bee pollinators. Conclusions: Our findings indicate that the N-fixing bacteria positively impact pollination, particularly when nutrients are limited. This study provides insights into the dynamics of plant–pollinator interactions and underscores the significant influence of root symbionts on key floral traits within tropical ecosystems. These results contribute to understanding the mechanisms governing mutualisms and their consequences for plant fitness and ecological dynamics.
Keywords: belowground interactions; Chamaecrista; mutualistic interactions; nitrogen fixation; pollinator attraction; tri-trophic interaction